Ultrafast time-resolved photoelectron and ion fragment momentum imaging of vacuum ultraviolet-excited molecules. Issue 7 (January 2020) - Slaughter, D S; Larsen, K A; Sturm, F P; Belkacem, A; Ranitovic, P; Weber, Th
Synopsis: New experimental results are presented on the dissociation dynamics of small neutral molecules in time-resolved photoexcitation-photoionization experiments by ultrashort vacuum- and extreme-ultraviolet laser pulses and charged particle momentum imaging.